Structural and virological identification of neutralizing antibody footprint provides insights into therapeutic antibody design against SARS-CoV-2 variants - Anraku, Yuki; Kita, Shunsuke; Onodera, Taishi; Sato, Akihiko; Tadokoro, Takashi; Ito, Shiori; Adachi, Yu; Kotaki, Ryutaro; Suzuki, Tateki; Sasaki, Jiei; Shiwa-Sudo, Nozomi; Iwata-Yoshikawa, Naoko; et al. (Communications biology, 2025)
Medical treatments using potent neutralizing SARS-CoV-2 antibodies have achieved remarkable improvements in clinical symptoms, changing the situation for the severity of COVID-19 patients. We previously reported an antibody, NT-108 with potent neutralizing activity. However, the structural and functional basis for the neutralizing activity of NT-108 has not yet been understood. Here, we demonstrated the therapeutic effects of NT-108 in a hamster model and its protective effects at low doses. Furthermore, we determined the cryo-EM structure of NT-108 in complex with SARS-CoV-2 spike. The single-chain Fv construction of NT-108 improved the cryo-EM maps because of the prevention of preferred orientations induced by Fab orientation. The footprints of NT-108 illuminated how escape mutations such as E484K evade from class 2 antibody recognition without ACE2 affinity attenuation. The functional and structural basis for the potent neutralizing activity of NT-108 provides insights into the rational design of therapeutic antibodies. A SARS-CoV-2 antibody, NT-108, exhibits potent therapeutic effects in vivo. Cryo-EM structure of the spike complexed with single-chain Fv of NT108 reveals its neutralizing mechanism, providing insight into antibody therapeutic design.